COMPARISON OF T WAVE ALTERNANS IN PATIENTS WITH ISCHEMIC AND NON-ISCHEMIC CARDIOMYOPATHY - Ashraf, Hira; Imran, Madiha; Naeem, Sara; Khan, Muhammad Alamgir (Pakistan Journal of Physiology, 2022)
Background: Early detection of T-wave alternans in patients with cardiomyopathy can help in risk stratification of ventricular arrhythmias leading to sudden cardiac death. The present study was designed to compare T-wave alternans in patients with ischemic and non-ischemic cardiomyopathy. Methods: This cross-sectional comparative study was carried out at Department of Cardiac Electrophysiology, Armed Forces Institute of Cardiology, Rawalpindi during 2019. Thirty patients with ischemic cardiomyopathy along with equal number of non-ischemic cardiomyopathy of matched age and gender were recruited through non-probability purposive sampling. Patients with diabetes mellitus, cerebrovascular accident, heart failure, bundle branch block, systemic arterial hypertension and ongoing anti-arrhythmic therapy were excluded from the study. DMS 300-4L Holters were used to obtain ambulatory ECG recordings. Cardio Scan Premier 12 Lux software was used for analysis of T-wave alternans. Results: A total of 60 subjects were studied. The mean value of T-wave alternans was 52.73±30.76 µV and 57.47±36.54 µV for patients with ischemic and non-ischemic cardiomyopathy respectively. The difference between mean values was statistically insignificant (p=0.59). T-wave alternans was present in 8 (26.7%) patients with ischemic cardiomyopathy, while 5 (16.7%) patients with non-ischemic cardiomyopathy showed positive T-wave alternans and the difference was statistically insignificant (p=0.35). Conclusion: The mean value of T-wave alternans and frequency of patients with positive T-wave alternans is not significantly different in ischemic and non-ischemic cardiomyopathy. Pak J Physiol 2022;18(1):9?12